PENERAPAN E-LKPD BERBASIS LIVEWORKSHEET DAPAT MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK FASE E DI SMA NEGERI 16 PADANG - Sheroja Ollina; Loli Setriani; Trina Febriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the implementation of Liveworksheet-based E-LKPD on increasing the learning motivation of phase E students at SMA Negeri 16 Padang. The problem found was the low learning motivation of students due to monotonous and uninteresting learning methods. The research method used was a quasi-experimental with a quantitative approach. The research sample consisted of two classes, namely E2 (experimental class, 39 students) and E1 (control class, 40 students), which were selected randomly. The research instruments were in the form of a learning motivation questionnaire and a pretest-posttest test. The results showed that the learning motivation of students in the experimental class increased significantly compared to the control class. The t-test showed a significance value of 0.001 <0.05, which means Ha is accepted. Thus, Liveworksheet-based E-LKPD is effective in increasing student learning motivation.